Application of Temperature and Humidity Control Technology in The Oyster Mushroom Cultivation Business - Erwin Ardias Saputra; Yuli Asmi Rahman; Rudi Santoso; Resky Tegar (Journal of Innovation and Community Engagement, 2024)
Temperature and humidity are critical factors in oyster mushroom cultivation, and as such, it is imperative to manage and regulate these variables with the aid of modern technology. The primary goal of this community service initiative is to enhance the productivity and quality of oyster mushrooms, while also fostering the sustainability of cultivation efforts. This method encompasses training sessions on proper temperature and humidity control techniques, the implementation of monitoring equipment, and the establishment of an optimal cultivation environment. The outcomes of these efforts have revealed a notable enhancement in both the production and quality of oyster mushrooms. Additionally, farmers have expressed an increase in technical knowledge and a deeper understanding of the advantages associated with appropriate environmental control. This technology holds the potential to elevate farmers' income and positively influence the cultivation environment. In summary, the implementation of temperature and humidity control technology yields tangible benefits, ultimately promoting the sustainability of oyster mushroom cultivation and contributing to the enhancement of farmers' expertise.